Recurrent Pregnancy Loss: An update - Samina Mohyiddin; Syed Tousif Ahmed (ziauddin University, 2024)
Recurrent pregnancy loss (RPL), a very distressing situation for the patient and physician, occurs in 1-5% of women who conceive. The cause of recurrent miscarriage is multifactorial, it may be caused by thrombotic, fibrinolytic, genetic, infectious, chromosomal, anatomic, endocrine, or immune abnormalities, but more than 33% of cases remain unexplained. Thrombophilic and fibrinolytic defects are raising issues regarding the cause of RPL. Fibrinolysis is a novel research avenue in the recurrent miscarriage field. A systematic review to explore the risk factors of recurrent pregnancy loss was done. Articles that contained population based, epidemiological and prospective studies were selected and data concerned with prevalence, possible etiology and future directions of RPL was compiled. The objective of this review is to appraise and explore the latest research in the field of different causes of recurrent miscarriage especially fibrinolysis, a new area of research, which needs to be explored by randomized studies, meta-analysis and systematic reviews. Well designed multicentre research trials with large sample size are necessary to produce strong evidence-based medicine. Key Words: RPL (Recurrent Pregnancy Loss), Thrombophilia, Fibrinolysis, PAI-1(Plasminogen Activator Inhibitor-1).